Successful Treatment of Inflammatory Linear Verrucous Epidermal Nevus with Concomitant Psoriasis Using Etanercept - Reda Hesham Saifaldeen; Mohammad I. Fatani; Badee Baltow; Abdulmajeed S. Khan (Karger Publishers, 2018)
Linear psoriasis is a rare form of the disease characterized by the linear distribution of lesions involving dermatome or along Blaschko's lines. Clinically, it may resemble inflammatory linear verrucous epidermal nevus; a combination of history, skin examination, and histopathology are required to ensure correct diagnosis and appropriate therapy. This paper describes a case of a 23-year-old male presenting with unilateral erythematous scaly plaques arranged in a linear path on the left leg. Etanercept was initiated after poor response to adalimumab. Improvement of his psoriasis was noted, with PASI 75 reduction after 24 weeks of treatment. Clinical studies have shown excellent efficacy of etanercept, and our patient well tolerated treatment with etanercept for 52 weeks without any adverse effects.